2014
DOI: 10.4236/ojra.2014.43026
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Secondary Bone Cancer in Lomé (Togo)

Abstract: Objectives: To determine the epidemiological, clinical and paraclinical profile of bone metastases cancer. Patients and Methods: It was a retrospective study performed on a series of cases, admitted in Rheumatology department of the University Teaching Hospital of Lomé, Togo from October 1989 to December 2008. The diagnosis of bone metastasis was made because of the existence of inflammatory bone pain, or pathological fracture, or bone swelling and a bone condensing or mixed or osteolytic radiological image. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 11 publications
(17 reference statements)
1
4
1
Order By: Relevance
“…These lesions mainly sit on pelvis, spine and femur. This distribution of the lesions was found by Oniankitan [6]. The achievement of the long bones was present in 18.2% of their patients.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…These lesions mainly sit on pelvis, spine and femur. This distribution of the lesions was found by Oniankitan [6]. The achievement of the long bones was present in 18.2% of their patients.…”
Section: Discussionsupporting
confidence: 58%
“…Although Tubiana-Hulin has reported that bone metastases accounted for over 90% of malignant disease of the bone [5], they are relatively rare in our series (51 patients had bone metastases over 15 years) and other African series like the recently published works (77 cases in 19 years in Togo and 81 cases in 7 years in Congo) [6] [7]. The frequency of bone metastases is certainly underestimated in the world.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations